2022
DOI: 10.1155/2022/2835258
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic Rubber Band-Assisted Endoscopic Submucosal Dissection: An Efficient Method for Treating Superficial Colorectal Tumors

Abstract: Background. Colorectal endoscopic submucosal dissection (ESD) is a complex operation. Effective traction is crucial. We have successfully used an orthodontic rubber band (ORB) combined with the clip traction method to assist ESD (ORB-ESD). The aim of this retrospective study is to describe the method and to compare the efficacy and safety of ORB-ESD versus conventional ESD in the treatment of superficial colorectal tumors. Methods. We retrospectively analyzed the data of patients with superficial colorectal tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…It comes in various diameters, has good elasticity, is cheap, and can be passed through the endoscope working channel. We showed in our previous study that the ESD procedure could be shortened by using ORB with a clip to assist ESD of colorectal tumors [ 7 ]. Therefore, we hypothesized that the use of ORB to assist gastric ESD could improve its efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It comes in various diameters, has good elasticity, is cheap, and can be passed through the endoscope working channel. We showed in our previous study that the ESD procedure could be shortened by using ORB with a clip to assist ESD of colorectal tumors [ 7 ]. Therefore, we hypothesized that the use of ORB to assist gastric ESD could improve its efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, various ESD traction methods continued to emerge in recent years [ 6 ], all showing advantages and disadvantages. Our previous report showed that the combined orthodontic rubber band (ORB) and clip traction-assisted ESD achieved good results in colorectal tumors [ 7 ]. ORBs are cheap, simple to operate, safe, and effective in the ESD procedure.…”
Section: Introductionmentioning
confidence: 99%
“…We showed in our previous study that the ESD procedure could be shortened by using ORB with a clip to assist ESD of colorectal tumors. 7 Therefore, we hypothesized that the use of ORB to assist gastric ESD could improve its e ciency.…”
Section: Discussionmentioning
confidence: 99%
“…Our experience suggests that placing a clip to clamp the rubber band to the opposite side of the lesion can reestablish effective traction. 7 Therefore, the ESD procedure may be shortened by re-inserting a new ORB for traction when dissecting lesions larger than 20 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation